Dementia and social inclusion : marginalised groups and marginalised areas of dementia research, care and practice - Innes, Anthea; Archibald, Carole; Murphy, Charlie, 1960- (Jessica Kingsley, 2004)
Examining important issues in dementia research and care that are often neglected or marginalized, the contributors to this book provide fresh perspectives on current practice. The authors put dementia care into a socio-cultural framework, highlighting the impact of social change on dementia care over the last two decades and challenging current stereotypes. The contributors address the implications of power relationships between carers and people with dementia and take an in-depth look at a broad spectrum of issues, including: the sexuality of people with dementia; communication and risk taki.